Danger signs of unethical behavior: How to determine if your firm is at ethical risk - Cooke, Robert Allan (Journal of business ethics, 1991)
This paper is designed to do three things. First, it discusses some of the key trends in business ethics in the academic and corporate communities. Initiatives like the Arthur Andersen Business Ethics Program are noted. Secondly, the paper examines certain basic misconceptions about the field and concludes that the adage that good ethics is good business is still true. Finally, the paper highlights fourteen business attitudes or practices that may put a firm at ethical risk. For example, the paper discusses the risk of using ethics as simply a public relations initiative., Man's life is not a state of unalloyed happiness. The earth is no paradise. Although this is not the fault of social institutions, people are wont to hold them responsible for it. The foundation of any and every civilization, including our own, is private ownership of the means of production. Whoever wishes to criticize modern civilization, therefore, begins with private property. It is blamed for everything that does not please the critic, especially those evils that have their origin in the fact that private property has been hampered and restrained in various respects so that its full social potentialities cannot be realized.1 , Ludwig von Mises